Analyzing Determinants of Mobile Banking Adoption in the Context of Indonesian Sharia Banks: A UTAUT 3 Framework - Indana, Rifaatul; Atika, Rindi (Al-Mashrof: Islamic Banking and Finance, 2023)
Mobile Banking become one of the main components in digital strategy. Bank Syariah Indonesia also provides BSI services Mobile. BSI usersMobile continues to increase but not yet comparable to the total number of BSI customers. This study aims to determine the factors that influence behavioral intention in using Mobile Banking BSI. In this study applying quantitative methods and using the theory of UTAUT-3. This study took a sample of Islamic banking students in Yogyakarta. The research was analyzed using the SEM approach (Structural Equation Model) PLS based (Partial Least Square). The statistical test results show that the Facilitating Conditions (Facilitating Conditions) and Price Value (Price Value) influencing intention in usage behavior Mobile Banking BSI to Islamic Banking students in Yogyakarta. Keywords:UTAUT 3, Mobile Banking, Behavioral Intentions